NILAI KARAKTER ISLAMI DALAM TUNJUK AJAR MELAYU TENAS EFFENDY - H. Putera, Griven (Jurnal Ilmu Budaya, 2020)
Tunjuk Ajar Melayu written by Tenas Effendy is a brilliant work that contains a variety of educational pearl values ​​in a broad sense. If the value is actualized in the concepts of education, then a quality form or format will be produced in the preparation of the concept of education. One of the most urgent values ​​in Malay teaching is character. Based on a study of the character content in the 2013 Curriculum and the character values ​​in the Tenas Effendy Malay Language Teaching Guide, the author sees that there are similarities and meeting points of the two aspects. However, the character values ​​in Tunjuk Ajar Melayu by Tenas Effendy are far broader and deeper and it touches directly on the cultural basis of society. These values ​​are neatly packaged in the curriculum, they will result a very positive if these impact in the context of achieving national education goals today.